Circulating tumor DNA functions as an alternative for tissue to overcome tumor heterogeneity in advanced gastric cancer. Issue 9 (29th July 2017) - Gao, Jing; Wang, Haixing; Zang, Wanchun; Li, Beifang; Rao, Guanhua; Li, Lei; Yu, Yang; Li, Zhongwu; Dong, Bin; Lu, Zhihao; Jiang, Zhi; Shen, Lin
Abstract : Overcoming tumor heterogeneity is a major challenge for personalized treatment of gastric cancer, especially for human epidermal growth factor receptor‐2 targeted therapy. Analysis of circulating tumor DNA allows a more comprehensive analysis of tumor heterogeneity than traditional biopsies in lung cancer and breast cancer, but little is known in gastric cancer. We assessed mutation profiles of ctDNA and primary tumors from 30 patients with advanced gastric cancer, then performed a comprehensive analysis of tumor mutations by multiple biopsies from five patients, and finally analyzed the concordance of HER2 amplification in ctDNA and paired tumor tissues in 70 patients. By comparing with a single tumor sample, ctDNA displayed a low concordance of mutation profile, only approximately 50% (138/275) somatic mutations were found in paired tissue samples, however, when compared with multiple biopsies, most DNA mutations in ctDNA were also shown in paired tumor tissues. ctDNA had a high concordance (91.4%, Kappa index = 0.784, P < 0.001) of HER2 amplification with tumor tissues, suggesting it might be an alternative for tissue. It implied that ctDNA‐based assessment could partially overcome the tumor heterogeneity, and might serve as a potential surrogate for HER2 analysis in gastric cancer. Abstract : Here we compared the somatic mutation detected from of plasma ctDNA and paired primary tumors in patients with AGC using targeted next‐generation sequencing. Heterogeneity and homogeneity co‐existed in gastric cancer tumor tissues and paired plasma, and plasma ctDNA could partially overcome the tumor heterogeneity. Our results imply that tumor tissues and paired plasma samples could be complementary and that both should be examined in the future era of precision medicine.